PENGARUH VIRAL MARKETING DAN BRAND AMBASSADOR TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPERCAYAAN PELANGGAN SEBAGAI VARIABEL MODERASI - Safatulloh, Erlangga Pratama; Wiratama, Dadang (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to analyze the influence of viral marketing and brand ambassadors on purchasing decisions with customer trust as a moderating variable. Using a quantitative approach, data were collected through a survey of 100 respondents. Analysis techniques include multiple linear regression tests and MRA tests. The results of the study indicate that viral marketing has a significant positive effect on purchasing decisions, brand ambassadors have a significant negative effect on purchasing decisions, and customer trust significantly moderates the relationship between brand ambassadors and purchasing decisions, but not on the relationship between viral marketing. These findings are examined within the framework of the Uses and Gratifications theory, which explains how individuals use media to meet information and social needs that motivate purchasing actions. In conclusion, the effectiveness of a marketing strategy depends on the emotional appeal and trust mediated by the brand ambassador.